BIOLOGICAL EFFECTS OF BETA GLUCAN EXTRACTED AND MEDICAL USE - Chamnanmoh, Palida (Journal of MCU Nakhondhat, 2023)
Beta - glucan is a polymer of glucose commonly found in fungi, bacteria, yeast, oats, barley, and rice. The molecular structure of beta-glucan consists of a central 1,3 - glucan backbone linked by 1,6 - glucosidic bonds, forming a chain connected by long side branches. The structure can vary depending on the source and extraction method. The biological properties of beta-glucan vary based on its origin, extraction methods, and water solubility. Notably, beta-glucan is recognized for its potent immunomodulatory properties, acting as a non-specific biological immune modifier. It has been developed into various nutritional supplements, taking different forms. Beta - glucan has also demonstrated other intriguing biological properties such as hypocholesterolemic effects, resistance to insulin, and potential anti - tumor effects. Studies have shown that beta-glucan derived from oats possesses hypocholesterolemic effects, while beta - glucan from rice exhibits insulin resistance. Beta - glucan from mushrooms, particularly Lentinan extracted from shiitake mushrooms, has anti-tumor properties, inhibiting the growth and spread of cancer cells. Moreover, beta - glucan has been studied for its wound healing properties and its ability to modulate sugar utilization in body cells. The versatility of beta - glucan extends to its application in the food industry, where it can be used to form gels. This review aims to provide a comprehensive understanding of the biological properties of various types of beta - glucans, exploring their potential benefits in different aspects of human health. However, it's important to note that while beta - glucan shows promise in various areas, there is currently no conclusive evidence supporting its use for preventing or treating diseases.